HUBUNGAN PENGETAHUAN DAN SLKAP LBU TENTANG GLZL, ASUPAN PROTELN DAN SENG ANAK, SERTA SANLTASI RUMAH TERHADAP STUNTLNG ANAK SEKOLAH DASAR - Kholidah, Nur; Rahfiluddin, M. Zen; Pangestuti, Dina Rahayu (Jurnal Kesehatan Masyarakat (e-Journal), 2020)
Primary school age 1 children is a period where children begin to enter school age and the school environment, where later children will also experience rapid physical, intelligence, mental, and emotional growth. Stunting is a form of stunted growth and development of children caused by long-term malnutrition and infectious diseases. The growth of elementary school age children requires intake of macro nutrients and micro nutrients. Protein has a function in the growth and maintenance of tissues, one of the main producers of energy, part of enzymes and antibodies, transporting nutrients and regulating water balance. While Zinc plays a role in body tissue, especially in the process of growth. The need for zinc is physiologically increased during periods of rapid growth due to the process of DNA replication, DNA transcription and endocrine function. If both of these nutrients are reduced then stunted growth for child development. The purpose of this study was to determine the relationship between mother's knowledge and attitudes about nutrition, protein intake and zinc in children, and home sanitation to stunting of elementary school children. Quantitative research methods with a cross sectional approach. The number of samples was 66 students. Data analysis used chi square, fisher exact test and Spearman rank. The analysis showed a correlation between mother's knowledge and attitudes about nutrition with the incidence of stunting (p <0.05) and the absence of a relationship between protein intake and children's zinc and home sanitation with the incidence of stunting (p> 0.05). However, confounding variables showed a relationship between maternal height and history of infection with stunting (p <0.05). It is suggested to mothers that given the importance of knowledge and good attitudes from mothers regarding child development and nutrition, it is recommended that the health department provide information to mothers or prospective mothers regarding the importance of nutrition to children. It aims to minimize the incidence of stunting in children.